Perception of Corporate Hypocrisy in China: The Roles of Corporate Social Responsibility Implementation and Communication - Zhao, Yiqi; Qin, Yuanjian; Zhao, Xianfeng; Wang, Xiao; Shi, Leilei (Frontiers in Psychology, 2020)
In the past two decades, corporate hypocrisy has become a phenomenon that cannot be ignored in CSR practice (Wanger et al., 2009), thus been concerned by management scholars (Cho et al., 2019). Using smartPLS, based on attribution theory, this paper takes 28 Chinese listed enterprises as examples to explore the influence of Corporate Social Responsibility (CSR) motivation perception on communication and implementation, as well as the impact of CSR implementation and promotion on consumers' perception of corporate hypocrisy.The research finds the negative correlation between value-driven motivation and corporate hypocrisy and the positive correlation between performance-driven motivation and stakeholder driven motivation and corporate hypocrisy.The theoretical contribution of this paper is mainly reflected in the following four aspects:(1) It describes the scale of CSR implementation research, and enriched the measurement tools of CSR implementation.(2) It enriched and expanded the research results in the field of CSR motivation perception.From the perspective of CSR and attribution theory, this study explored the influence of consumers' perception of CSR motivation on CSR communication and CSR implementation.(3) It supplemented the research results in the field of corporate hypocrisy.The influence of CSR communication and CSR implementation on corporate hypocrisy is clarified.(4) It clarified the impact of CSR communication on CSR implementation, so as to help enterprises better match CSR communication strategy and CSR implementation in practice, and reduce consumers' perception of corporate hypocrisy.It is suggested that enterprises find their own positioning on CSR motivation, which provides a reference for enterprises to make better decisions on CSR communication strategy after implementing CSR behavior, and provides empirical evidence for the research on CSR motivation perception and corporate hypocrisy in China.